2006
DOI: 10.1007/s10803-006-0339-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Vocal-Motor Development in Infant Siblings of Children with Autism

Abstract: In this study we examined early motor, vocal, and communicative development in a group of younger siblings of children diagnosed with autism (Infant Siblings). Infant Siblings and no-risk comparison later-born infants were videotaped at home with a primary caregiver each month from 5 to 14 months, with follow-up at 18 months. As a group, Infant Siblings were delayed in the onset of early developmental milestones and spent significantly less time in a greater number of postures, suggestive of relative postural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(203 citation statements)
references
References 52 publications
7
187
2
7
Order By: Relevance
“…The focus centered specifically on young children under the age of three 24 years. The results obtained are consistent with the current body of literature on ASD with respect to deficits in the areas of cognitive, language, social-emotional and adaptive skills (Cognition: Stone et al, 2007, Toth et al, 2006Language: Chawarska et al, 2007;Iverson & Wozniak, 2007;Landa & Garret-Mayer, 2006;Social-emotional: Chawarska et al, 2007;Zwaigenbaum et al, 2005;Adaptive: Green & Carter, 2014).…”
Section: Developmental Motor Scales-2 Nd Edition (Pdms-2) Results Desupporting
confidence: 89%
See 2 more Smart Citations
“…The focus centered specifically on young children under the age of three 24 years. The results obtained are consistent with the current body of literature on ASD with respect to deficits in the areas of cognitive, language, social-emotional and adaptive skills (Cognition: Stone et al, 2007, Toth et al, 2006Language: Chawarska et al, 2007;Iverson & Wozniak, 2007;Landa & Garret-Mayer, 2006;Social-emotional: Chawarska et al, 2007;Zwaigenbaum et al, 2005;Adaptive: Green & Carter, 2014).…”
Section: Developmental Motor Scales-2 Nd Edition (Pdms-2) Results Desupporting
confidence: 89%
“…Results found that children with ASD demonstrated a progressive receptive and expressive language regression around 14 months of age. Furthermore, deficits in the frequency and prosodic features of vocalizations (Chawarska et al, 2007), delayed onset of babbling (Iverson & Wozniak, 2007) and usage of gestures and pointing as a communicative tool (Chawarska et al, 2007) have all be documented between one and two years of age.…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Pickles and Angold (2003) state, in order to understand the relationships between psychopathology, its aetiology, outcome and other factors, "we need to adopt a truly empirical approach that is unblinkered by either categorical or dimensional prejudices" (p548). Retrospective studies of early predictors of psychopathology are limited by issues of recall bias while prospective cohorts of subjects at 'high risk' (Besag, 2006;Cassell et al, 2007;Gamliel, Yirmiya, & Sigman, 2007;Iverson & Wozniak, 2007;Landa, Garrett-Mayer, Landa, & Garrett-Mayer, 2006;Loh et al, 2007;Merin, Young, Ozonoff, & Rogers, 2007;Toth, Dawson, Meltzoff, Greenson, & Fein, 2007;Yirmiya et al, 2006;Zwaigenbaum et al, 2005b;Yirmiya et al, 2007;Zwaigenbaum et al, 2005a;Zwaigenbaum et al, 2005a) may reveal early indicators of neurodevelopmental disorders, such as autism, but are subject to a variety of forms of selection and ascertainment bias. For example, prospective studies of children exposed to smoking in pregnancy and of children with very low birth weights have shown increased rates of ADHD and of ADHD/autism symptoms (Hultman et al, 2007;Indredavik, Brubakk, Romundstad, & Vik, 2007), but to what extent such factors alone can contribute to these difficulties can best be determined in the context of general population birth cohort studies.…”
Section: Problems With Existing Studies Of Early Neurodevelopment Andmentioning
confidence: 99%
“…In a study of 17 children with ASD (Gernsbacher et al, 2008), 15% presented with oral dyspraxia. Difficulty in oral movements at an early age was a negative factor in the development of speech (Iverson & Wozniak, 2007;Page & Boucher, 1998;Seal & Bonvillion, 1997). Also, in a longitudinal study of seven years, Anderson et al (2007) found that at the age of 9 years 29.7% of the children who participated in the study never developed speech.…”
Section: Discussionmentioning
confidence: 99%